2018
DOI: 10.1080/02713683.2018.1433859
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Mid-Wavelength Photoresponsivity in the Mouse Retina

Abstract: Purpose Photoreceptors in the mouse retina express much of the molecular machinery necessary for phototransduction and glutamatergic transmission prior to eye opening at postnatal day 13. Light responses have been observed collectively from rod and cone photoreceptors via electroretinogram recordings as early as postnatal day 13 (P13) in mouse, and the responses are known to become more robust with maturation, reaching a mature state by P30. Photocurrents from single rod outer segments have been recorded at P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In summary, ERGs can be obtained from a living animal (in vivo set-up) (He et al 2013;Vinberg et al 2014;Tian et al 2015;Vinberg & Kefalov, 2015) or from ex vivo set-ups, as demonstrated here and in previous studies (Donner et al 1988;Heikkinen et al 2008Heikkinen et al , 2012Vinberg et al 2014;Vinberg & Kefalov, 2015;Sakurai et al 2016;Bonezzi et al 2018). Ex vivo ERGs detect transretinal voltage deflections in response to different wavelengths and intensities of light stimuli, with responses comparable, in their amplitudes and kinetics to in vivo studies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In summary, ERGs can be obtained from a living animal (in vivo set-up) (He et al 2013;Vinberg et al 2014;Tian et al 2015;Vinberg & Kefalov, 2015) or from ex vivo set-ups, as demonstrated here and in previous studies (Donner et al 1988;Heikkinen et al 2008Heikkinen et al , 2012Vinberg et al 2014;Vinberg & Kefalov, 2015;Sakurai et al 2016;Bonezzi et al 2018). Ex vivo ERGs detect transretinal voltage deflections in response to different wavelengths and intensities of light stimuli, with responses comparable, in their amplitudes and kinetics to in vivo studies.…”
Section: Discussionsupporting
confidence: 52%
“…Alternatively, ex vivo recordings require isolation of the retina from the eye-cup, but are more sensitive and often exhibit a higher signal-to-noise ratio. Numerous studies have demonstrated this, making the ex vivo configuration the superior option when interested in studying smaller responses, including cone-evoked responses and those from immature tissue (Kolesnikov & Kefalov, 2012;Vinberg et al 2014;Vinberg & Kefalov, 2015;Sakurai et al 2016;Bonezzi et al 2018). Another benefit of this recording configuration is that it permits rapid perfusion of pharmacological agents, thereby isolating desired cellular contributions to the ERG waveform.…”
Section: Introductionmentioning
confidence: 99%
“…Melanopsin-mediated photosensitivity is the earliest means of light detection in the mammalian retina (Rao et al, 2013; Sekaran et al, 2005; Tu et al, 2005), and it is thought to be the predominant means of photosensitivity prior to rod- and cone-driven light responses, which emerge just before eye opening at around post-natal day (P)8 and drive ganglion cells to spike as early as P10 (Bonezzi et al, 2018; Schmidt et al, 2008; Tian and Copenhagen, 2003). As ipRGCs send ORDs to the outer retina during the first 2 post-natal weeks of life (Renna et al, 2015; Sondereker et al, 2017), we hypothesized that ipRGCs may be involved in organizing aspects of retinal architecture.…”
Section: Resultsmentioning
confidence: 99%
“…S-opsin expression is detectable as early as E15.5 (Aavani et al, 2017), but it is believed that immature cones (i.e., before P8) do not functionally respond to light due to their lack of outer segments and underdeveloped ribbon synapse (Bakall et al, 2003; Bonezzi et al, 2018; Rich et al, 1997). To directly test whether light was acting through ipRGCs to influence cone lamination, we manipulated early photosensitivity independently in cones and ipRGCs using genetic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Conversion of T4 to T3 occurs locally in target tissues to induce gene expression responses (34,35). Deiodinases, enzymes that modulate the levels of T3 and T4, are expressed in the retinas of mice, fish, and chicken (29,(36)(37)(38)(39)(40).…”
Section: Dynamic Expression Of Thyroid Hormone-regulating Genes Durinmentioning
confidence: 99%